Persistent gender differences in spatial ability, even in STEM experts - Elina S. Tsigeman; Maxim V. Likhanov; Anna V. Budakova; Aydar Akmalov; Ildar Sabitov; Evgeniia Alenina; Ksenia Bartseva; Yulia Kovas (Heliyon, 2023)
Background: Spatial ability (SA) shows wide variability. One proposed explanation for the observed individual difference in SA is variability in interest and engagement in activities that promote spatial ability. Research also robustly shown that males on average outperform females in most aspects of SA. Previous studies have identified a number of activities that can potentially contribute to both individual and gender differences in SA, including tinkering with electronics, particular sports activities, and designing. However, the findings regarding these links are inconsistent. One way to investigate these links is to compare the groups that are intensively engaged with these activities. Aim: The present study aims to evaluate the robustness of these links by comparing SA in adolescents with expertise in STEM, arts, and sports, with their unselected peers. We also aimed to assess whether gender differences in SA are still present in expert groups. Methods: The data on ten small-scale SA tests was collected in an unselected sample of adolescents (N = 864, Mean age = 15.4, SD = 1.1); as well as in 3 samples of adolescents with expertise in STEM (N = 667, Mean age = 15, SD = 1.2); in Arts (N = 280, Mean age = 15, SD = 1.2) and in Sports (N = 444, Mean age = 14.3, SD = 0.7). Results: Out of the three expert groups, only STEM experts on average outperformed the unselected group on all SA tasks. The STEM experts also outperformed Arts and Sports experts. Gender differences persisted in all expert groups, with moderate effect sizes. Discussion: Findings support previously established links between spatial ability and STEM-related expertise. In contrast, such links were not found for expertise in arts and sports. Consistent with previous research, we found gender differences in SA for all samples, which persisted in STEM experts.